# Theory Harmonic_Numbers

```(*  Title:    HOL/Analysis/Harmonic_Numbers.thy
Author:   Manuel Eberl, TU München
*)

section ‹Harmonic Numbers›

theory Harmonic_Numbers
imports
Complex_Transcendental
Summation_Tests
begin

text ‹
The definition of the Harmonic Numbers and the Euler-Mascheroni constant.
Also provides a reasonably accurate approximation of \<^term>‹ln 2 :: real›
and the Euler-Mascheroni constant.
›

subsection ‹The Harmonic numbers›

definition✐‹tag important› harm :: "nat ⇒ 'a :: real_normed_field" where
"harm n = (∑k=1..n. inverse (of_nat k))"

lemma harm_altdef: "harm n = (∑k<n. inverse (of_nat (Suc k)))"
unfolding harm_def by (induction n) simp_all

lemma harm_Suc: "harm (Suc n) = harm n + inverse (of_nat (Suc n))"

lemma harm_nonneg: "harm n ≥ (0 :: 'a :: {real_normed_field,linordered_field})"
unfolding harm_def by (intro sum_nonneg) simp_all

lemma harm_pos: "n > 0 ⟹ harm n > (0 :: 'a :: {real_normed_field,linordered_field})"
unfolding harm_def by (intro sum_pos) simp_all

lemma harm_mono: "m ≤ n ⟹ harm m ≤ (harm n :: 'a :: {real_normed_field,linordered_field})"

lemma of_real_harm: "of_real (harm n) = harm n"
unfolding harm_def by simp

lemma abs_harm [simp]: "(abs (harm n) :: real) = harm n"
using harm_nonneg[of n] by (rule abs_of_nonneg)

lemma norm_harm: "norm (harm n) = harm n"
by (subst of_real_harm [symmetric]) (simp add: harm_nonneg)

lemma harm_expand:
"harm 0 = 0"
"harm (Suc 0) = 1"
"harm (numeral n) = harm (pred_numeral n) + inverse (numeral n)"
proof -
have "numeral n = Suc (pred_numeral n)" by simp
also have "harm … = harm (pred_numeral n) + inverse (numeral n)"
by (subst harm_Suc, subst numeral_eq_Suc[symmetric]) simp
finally show "harm (numeral n) = harm (pred_numeral n) + inverse (numeral n)" .

theorem not_convergent_harm: "¬convergent (harm :: nat ⇒ 'a :: real_normed_field)"
proof -
have "convergent (λn. norm (harm n :: 'a)) ⟷
convergent (harm :: nat ⇒ real)" by (simp add: norm_harm)
also have "… ⟷ convergent (λn. ∑k=Suc 0..Suc n. inverse (of_nat k) :: real)"
unfolding harm_def[abs_def] by (subst convergent_Suc_iff) simp_all
also have "... ⟷ convergent (λn. ∑k≤n. inverse (of_nat (Suc k)) :: real)"
by (subst sum.shift_bounds_cl_Suc_ivl) (simp add: atLeast0AtMost)
also have "... ⟷ summable (λn. inverse (of_nat n) :: real)"
by (subst summable_Suc_iff [symmetric]) (simp add: summable_iff_convergent')
also have "¬..." by (rule not_summable_harmonic)
finally show ?thesis by (blast dest: convergent_norm)
qed

lemma harm_pos_iff [simp]: "harm n > (0 :: 'a :: {real_normed_field,linordered_field}) ⟷ n > 0"
by (rule iffI, cases n, simp add: harm_expand, simp, rule harm_pos)

lemma ln_diff_le_inverse:
assumes "x ≥ (1::real)"
shows   "ln (x + 1) - ln x < 1 / x"
proof -
from assms have "∃z>x. z < x + 1 ∧ ln (x + 1) - ln x = (x + 1 - x) * inverse z"
by (intro MVT2) (auto intro!: derivative_eq_intros simp: field_simps)
then obtain z where z: "z > x" "z < x + 1" "ln (x + 1) - ln x = inverse z" by auto
have "ln (x + 1) - ln x = inverse z" by fact
also from z(1,2) assms have "… < 1 / x" by (simp add: field_simps)
finally show ?thesis .
qed

lemma ln_le_harm: "ln (real n + 1) ≤ (harm n :: real)"
proof (induction n)
fix n assume IH: "ln (real n + 1) ≤ harm n"
have "ln (real (Suc n) + 1) = ln (real n + 1) + (ln (real n + 2) - ln (real n + 1))" by simp
also have "(ln (real n + 2) - ln (real n + 1)) ≤ 1 / real (Suc n)"
also note IH
also have "harm n + 1 / real (Suc n) = harm (Suc n)" by (simp add: harm_Suc field_simps)
finally show "ln (real (Suc n) + 1) ≤ harm (Suc n)" by - simp

lemma harm_at_top: "filterlim (harm :: nat ⇒ real) at_top sequentially"
proof (rule filterlim_at_top_mono)
show "eventually (λn. harm n ≥ ln (real (Suc n))) at_top"
show "filterlim (λn. ln (real (Suc n))) at_top sequentially"
by (intro filterlim_compose[OF ln_at_top] filterlim_compose[OF filterlim_real_sequentially]
filterlim_Suc)
qed

subsection ‹The Euler-Mascheroni constant›

text ‹
The limit of the difference between the partial harmonic sum and the natural logarithm
(approximately 0.577216). This value occurs e.g. in the definition of the Gamma function.
›
definition euler_mascheroni :: "'a :: real_normed_algebra_1" where
"euler_mascheroni = of_real (lim (λn. harm n - ln (of_nat n)))"

lemma of_real_euler_mascheroni [simp]: "of_real euler_mascheroni = euler_mascheroni"

lemma harm_ge_ln: "harm n ≥ ln (real n + 1)"
proof -
have "ln (n + 1) = (∑j<n. ln (real (Suc j + 1)) - ln (real (j + 1)))"
by (subst sum_lessThan_telescope) auto
also have "… ≤ (∑j<n. 1 / (Suc j))"
proof (intro sum_mono, clarify)
fix j assume j: "j < n"
have "∃ξ. ξ > real j + 1 ∧ ξ < real j + 2 ∧
ln (real j + 2) - ln (real j + 1) = (real j + 2 - (real j + 1)) * (1 / ξ)"
by (intro MVT2) (auto intro!: derivative_eq_intros)
then obtain ξ :: real
where ξ: "ξ ∈ {real j + 1..real j + 2}" "ln (real j + 2) - ln (real j + 1) = 1 / ξ"
by auto
note ξ(2)
also have "1 / ξ ≤ 1 / (Suc j)"
using ξ(1) by (auto simp: field_simps)
finally show "ln (real (Suc j + 1)) - ln (real (j + 1)) ≤ 1 / (Suc j)"
qed
also have "… = harm n"
qed

lemma decseq_harm_diff_ln: "decseq (λn. harm (Suc n) - ln (Suc n))"
proof (rule decseq_SucI)
fix m :: nat
define n where "n = Suc m"
have "n > 0" by (simp add: n_def)
have "convex_on {0<..} (λx :: real. -ln x)"
by (rule convex_on_realI[where f' = "λx. -1/x"])
(auto intro!: derivative_eq_intros simp: field_simps)
hence "(-1 / (n + 1)) * (real n - real (n + 1)) ≤ (- ln (real n)) - (-ln (real (n + 1)))"
using ‹n > 0› by (intro convex_on_imp_above_tangent[where A = "{0<..}"])
(auto intro!: derivative_eq_intros simp: interior_open)
thus "harm (Suc n) - ln (Suc n) ≤ harm n - ln n"
by (auto simp: harm_Suc field_simps)
qed

lemma euler_mascheroni_sequence_nonneg:
assumes "n > 0"
shows   "harm n - ln (real n) ≥ (0 :: real)"
proof -
have "ln (real n) ≤ ln (real n + 1)"
using assms by simp
also have "… ≤ harm n"
by (rule harm_ge_ln)
finally show ?thesis by simp
qed

lemma euler_mascheroni_convergent: "convergent (λn. harm n - ln n)"
proof -
have "harm (Suc n) - ln (real (Suc n)) ≥ 0" for n :: nat
using euler_mascheroni_sequence_nonneg[of "Suc n"] by simp
hence "convergent (λn. harm (Suc n) - ln (Suc n))"
by (intro Bseq_monoseq_convergent decseq_bounded[of _ 0] decseq_harm_diff_ln decseq_imp_monoseq)
auto
thus ?thesis
by (subst (asm) convergent_Suc_iff)
qed

lemma euler_mascheroni_sequence_decreasing:
"m > 0 ⟹ m ≤ n ⟹ harm n - ln (of_nat n) ≤ harm m - ln (of_nat m :: real)"
using decseqD[OF decseq_harm_diff_ln, of "m - 1" "n - 1"] by simp

lemma✐‹tag important› euler_mascheroni_LIMSEQ:
"(λn. harm n - ln (of_nat n) :: real) ⇢ euler_mascheroni"
unfolding euler_mascheroni_def
by (simp add: convergent_LIMSEQ_iff [symmetric] euler_mascheroni_convergent)

lemma euler_mascheroni_LIMSEQ_of_real:
"(λn. of_real (harm n - ln (of_nat n))) ⇢
(euler_mascheroni :: 'a :: {real_normed_algebra_1, topological_space})"
proof -
have "(λn. of_real (harm n - ln (of_nat n))) ⇢ (of_real (euler_mascheroni) :: 'a)"
by (intro tendsto_of_real euler_mascheroni_LIMSEQ)
thus ?thesis by simp
qed

lemma euler_mascheroni_sum_real:
"(λn. inverse (of_nat (n+1)) + ln (of_nat (n+1)) - ln (of_nat (n+2)) :: real)
sums euler_mascheroni"
telescope_sums'[OF LIMSEQ_inverse_real_of_nat]]

lemma euler_mascheroni_sum:
"(λn. inverse (of_nat (n+1)) + of_real (ln (of_nat (n+1))) - of_real (ln (of_nat (n+2))))
sums (euler_mascheroni :: 'a :: {banach, real_normed_field})"
proof -
have "(λn. of_real (inverse (of_nat (n+1)) + ln (of_nat (n+1)) - ln (of_nat (n+2))))
sums (of_real euler_mascheroni :: 'a :: {banach, real_normed_field})"
by (subst sums_of_real_iff) (rule euler_mascheroni_sum_real)
thus ?thesis by simp
qed

theorem alternating_harmonic_series_sums: "(λk. (-1)^k / real_of_nat (Suc k)) sums ln 2"
proof -
let ?f = "λn. harm n - ln (real_of_nat n)"
let ?g = "λn. if even n then 0 else (2::real)"
let ?em = "λn. harm n - ln (real_of_nat n)"
have "eventually (λn. ?em (2*n) - ?em n + ln 2 = (∑k<2*n. (-1)^k / real_of_nat (Suc k))) at_top"
using eventually_gt_at_top[of "0::nat"]
proof eventually_elim
fix n :: nat assume n: "n > 0"
have "(∑k<2*n. (-1)^k / real_of_nat (Suc k)) =
(∑k<2*n. ((-1)^k + ?g k) / of_nat (Suc k)) - (∑k<2*n. ?g k / of_nat (Suc k))"
by (simp add: sum.distrib algebra_simps divide_inverse)
also have "(∑k<2*n. ((-1)^k + ?g k) / real_of_nat (Suc k)) = harm (2*n)"
unfolding harm_altdef by (intro sum.cong) (auto simp: field_simps)
also have "(∑k<2*n. ?g k / real_of_nat (Suc k)) = (∑k|k<2*n ∧ odd k. ?g k / of_nat (Suc k))"
by (intro sum.mono_neutral_right) auto
also have "… = (∑k|k<2*n ∧ odd k. 2 / (real_of_nat (Suc k)))"
by (intro sum.cong) auto
also have "(∑k|k<2*n ∧ odd k. 2 / (real_of_nat (Suc k))) = harm n"
unfolding harm_altdef
by (intro sum.reindex_cong[of "λn. 2*n+1"]) (auto simp: inj_on_def field_simps elim!: oddE)
also have "harm (2*n) - harm n = ?em (2*n) - ?em n + ln 2" using n
finally show "?em (2*n) - ?em n + ln 2 = (∑k<2*n. (-1)^k / real_of_nat (Suc k))" ..
qed
moreover have "(λn. ?em (2*n) - ?em n + ln (2::real))
⇢ euler_mascheroni - euler_mascheroni + ln 2"
by (intro tendsto_intros euler_mascheroni_LIMSEQ filterlim_compose[OF euler_mascheroni_LIMSEQ]
filterlim_subseq) (auto simp: strict_mono_def)
hence "(λn. ?em (2*n) - ?em n + ln (2::real)) ⇢ ln 2" by simp
ultimately have "(λn. (∑k<2*n. (-1)^k / real_of_nat (Suc k))) ⇢ ln 2"
by (blast intro: Lim_transform_eventually)

moreover have "summable (λk. (-1)^k * inverse (real_of_nat (Suc k)))"
using LIMSEQ_inverse_real_of_nat
by (intro summable_Leibniz(1) decseq_imp_monoseq decseq_SucI) simp_all
hence A: "(λn. ∑k<n. (-1)^k / real_of_nat (Suc k)) ⇢ (∑k. (-1)^k / real_of_nat (Suc k))"
by (simp add: summable_sums_iff divide_inverse sums_def)
from filterlim_compose[OF this filterlim_subseq[of "(*) (2::nat)"]]
have "(λn. ∑k<2*n. (-1)^k / real_of_nat (Suc k)) ⇢ (∑k. (-1)^k / real_of_nat (Suc k))"
ultimately have "(∑k. (- 1) ^ k / real_of_nat (Suc k)) = ln 2" by (intro LIMSEQ_unique)
with A show ?thesis by (simp add: sums_def)
qed

lemma alternating_harmonic_series_sums':
"(λk. inverse (real_of_nat (2*k+1)) - inverse (real_of_nat (2*k+2))) sums ln 2"
unfolding sums_def
proof (rule Lim_transform_eventually)
show "(λn. ∑k<2*n. (-1)^k / (real_of_nat (Suc k))) ⇢ ln 2"
using alternating_harmonic_series_sums unfolding sums_def
by (rule filterlim_compose) (rule mult_nat_left_at_top, simp)
show "eventually (λn. (∑k<2*n. (-1)^k / (real_of_nat (Suc k))) =
(∑k<n. inverse (real_of_nat (2*k+1)) - inverse (real_of_nat (2*k+2)))) sequentially"
proof (intro always_eventually allI)
fix n :: nat
show "(∑k<2*n. (-1)^k / (real_of_nat (Suc k))) =
(∑k<n. inverse (real_of_nat (2*k+1)) - inverse (real_of_nat (2*k+2)))"
by (induction n) (simp_all add: inverse_eq_divide)
qed
qed

subsection✐‹tag unimportant› ‹Bounds on the Euler-Mascheroni constant›
(* TODO: perhaps move this section away to remove unnecessary dependency on integration *)

(* TODO: Move? *)
lemma ln_inverse_approx_le:
assumes "(x::real) > 0" "a > 0"
shows   "ln (x + a) - ln x ≤ a * (inverse x + inverse (x + a))/2" (is "_ ≤ ?A")
proof -
define f' where "f' = (inverse (x + a) - inverse x)/a"
let ?f = "λt. (t - x) * f' + inverse x"
let ?F = "λt. (t - x)^2 * f' / 2 + t * inverse x"

have deriv: "∃D. ((λx. ?F x - ln x) has_field_derivative D) (at ξ) ∧ D ≥ 0"
if "ξ ≥ x" "ξ ≤ x + a" for ξ
proof -
from that assms have t: "0 ≤ (ξ - x) / a" "(ξ - x) / a ≤ 1" by simp_all
have "inverse ξ = inverse ((1 - (ξ - x) / a) *⇩R x + ((ξ - x) / a) *⇩R (x + a))" (is "_ = ?A")
using assms by (simp add: field_simps)
also from assms have "convex_on {x..x+a} inverse" by (intro convex_on_inverse) auto
from convex_onD_Icc[OF this _ t] assms
have "?A ≤ (1 - (ξ - x) / a) * inverse x + (ξ - x) / a * inverse (x + a)" by simp
also have "… = (ξ - x) * f' + inverse x" using assms
finally have "?f ξ - 1 / ξ ≥ 0" by (simp add: field_simps)
moreover have "((λx. ?F x - ln x) has_field_derivative ?f ξ - 1 / ξ) (at ξ)"
using that assms by (auto intro!: derivative_eq_intros simp: field_simps)
ultimately show ?thesis by blast
qed
have "?F x - ln x ≤ ?F (x + a) - ln (x + a)"
by (rule DERIV_nonneg_imp_nondecreasing[of x "x + a", OF _ deriv]) (use assms in auto)
thus ?thesis
qed

lemma ln_inverse_approx_ge:
assumes "(x::real) > 0" "x < y"
shows   "ln y - ln x ≥ 2 * (y - x) / (x + y)" (is "_ ≥ ?A")
proof -
define m where "m = (x+y)/2"
define f' where "f' = -inverse (m^2)"
from assms have m: "m > 0" by (simp add: m_def)
let ?F = "λt. (t - m)^2 * f' / 2 + t / m"
let ?f = "λt. (t - m) * f' + inverse m"

have deriv: "∃D. ((λx. ln x - ?F x) has_field_derivative D) (at ξ) ∧ D ≥ 0"
if "ξ ≥ x" "ξ ≤ y" for ξ
proof -
from that assms have "inverse ξ - inverse m ≥ f' * (ξ - m)"
by (intro convex_on_imp_above_tangent[of "{0<..}"] convex_on_inverse)
(auto simp: m_def interior_open f'_def power2_eq_square intro!: derivative_eq_intros)
hence "1 / ξ - ?f ξ ≥ 0" by (simp add: field_simps f'_def)
moreover have "((λx. ln x - ?F x) has_field_derivative 1 / ξ - ?f ξ) (at ξ)"
using that assms m by (auto intro!: derivative_eq_intros simp: field_simps)
ultimately show ?thesis by blast
qed
have "ln x - ?F x ≤ ln y - ?F y"
by (rule DERIV_nonneg_imp_nondecreasing[of x y, OF _ deriv]) (use assms in auto)
hence "ln y - ln x ≥ ?F y - ?F x"
also have "?F y - ?F x = ?A"
using assms by (simp add: f'_def m_def divide_simps) (simp add: algebra_simps power2_eq_square)
finally show ?thesis .
qed

lemma euler_mascheroni_lower:
"euler_mascheroni ≥ harm (Suc n) - ln (real_of_nat (n + 2)) + 1/real_of_nat (2 * (n + 2))"
and euler_mascheroni_upper:
"euler_mascheroni ≤ harm (Suc n) - ln (real_of_nat (n + 2)) + 1/real_of_nat (2 * (n + 1))"
proof -
define D :: "_ ⇒ real"
where "D n = inverse (of_nat (n+1)) + ln (of_nat (n+1)) - ln (of_nat (n+2))" for n
let ?g = "λn. ln (of_nat (n+2)) - ln (of_nat (n+1)) - inverse (of_nat (n+1)) :: real"
define inv where [abs_def]: "inv n = inverse (real_of_nat n)" for n
fix n :: nat
note summable = sums_summable[OF euler_mascheroni_sum_real, folded D_def]
have sums: "(λk. (inv (Suc (k + (n+1))) - inv (Suc (Suc k + (n+1))))/2) sums ((inv (Suc (0 + (n+1))) - 0)/2)"
unfolding inv_def
by (intro sums_divide telescope_sums' LIMSEQ_ignore_initial_segment LIMSEQ_inverse_real_of_nat)
have sums': "(λk. (inv (Suc (k + n)) - inv (Suc (Suc k + n)))/2) sums ((inv (Suc (0 + n)) - 0)/2)"
unfolding inv_def
by (intro sums_divide telescope_sums' LIMSEQ_ignore_initial_segment LIMSEQ_inverse_real_of_nat)
from euler_mascheroni_sum_real have "euler_mascheroni = (∑k. D k)"
also have "… = (∑k. D (k + Suc n)) + (∑k≤n. D k)"
by (subst suminf_split_initial_segment[OF summable, of "Suc n"],
subst lessThan_Suc_atMost) simp
finally have sum: "(∑k≤n. D k) - euler_mascheroni = -(∑k. D (k + Suc n))" by simp

note sum
also have "… ≤ -(∑k. (inv (k + Suc n + 1) - inv (k + Suc n + 2)) / 2)"
proof (intro le_imp_neg_le suminf_le allI summable_ignore_initial_segment[OF summable])
fix k' :: nat
define k where "k = k' + Suc n"
hence k: "k > 0" by (simp add: k_def)
have "real_of_nat (k+1) > 0" by (simp add: k_def)
with ln_inverse_approx_le[OF this zero_less_one]
have "ln (of_nat k + 2) - ln (of_nat k + 1) ≤ (inv (k+1) + inv (k+2))/2"
hence "(inv (k+1) - inv (k+2))/2 ≤ inv (k+1) + ln (of_nat (k+1)) - ln (of_nat (k+2))"
also have "… = D k" unfolding D_def inv_def ..
finally show "D (k' + Suc n) ≥ (inv (k' + Suc n + 1) - inv (k' + Suc n + 2)) / 2"
from sums_summable[OF sums]
show "summable (λk. (inv (k + Suc n + 1) - inv (k + Suc n + 2))/2)" by simp
qed
also from sums have "… = -inv (n+2) / 2" by (simp add: sums_iff)
finally have "euler_mascheroni ≥ (∑k≤n. D k) + 1 / (of_nat (2 * (n+2)))"
also have "(∑k≤n. D k) = harm (Suc n) - (∑k≤n. ln (real_of_nat (Suc k+1)) - ln (of_nat (k+1)))"
unfolding harm_altdef D_def by (subst lessThan_Suc_atMost) (simp add:  sum.distrib sum_subtractf)
also have "(∑k≤n. ln (real_of_nat (Suc k+1)) - ln (of_nat (k+1))) = ln (of_nat (n+2))"
by (subst atLeast0AtMost [symmetric], subst sum_Suc_diff) simp_all
finally show "euler_mascheroni ≥ harm (Suc n) - ln (real_of_nat (n + 2)) + 1/real_of_nat (2 * (n + 2))"
by simp

note sum
also have "-(∑k. D (k + Suc n)) ≥ -(∑k. (inv (Suc (k + n)) - inv (Suc (Suc k + n)))/2)"
proof (intro le_imp_neg_le suminf_le allI summable_ignore_initial_segment[OF summable])
fix k' :: nat
define k where "k = k' + Suc n"
hence k: "k > 0" by (simp add: k_def)
have "real_of_nat (k+1) > 0" by (simp add: k_def)
from ln_inverse_approx_ge[of "of_nat k + 1" "of_nat k + 2"]
have "2 / (2 * real_of_nat k + 3) ≤ ln (of_nat (k+2)) - ln (real_of_nat (k+1))"
hence "D k ≤ 1 / real_of_nat (k+1) - 2 / (2 * real_of_nat k + 3)"
by (simp add: D_def inverse_eq_divide inv_def)
also have "… = inv ((k+1)*(2*k+3))" unfolding inv_def by (simp add: field_simps)
also have "… ≤ inv (2*k*(k+1))" unfolding inv_def using k
by (intro le_imp_inverse_le)
also have "… = (inv k - inv (k+1))/2" unfolding inv_def using k
finally show "D k ≤ (inv (Suc (k' + n)) - inv (Suc (Suc k' + n)))/2" unfolding k_def by simp
next
from sums_summable[OF sums']
show "summable (λk. (inv (Suc (k + n)) - inv (Suc (Suc k + n)))/2)" by simp
qed
also from sums' have "(∑k. (inv (Suc (k + n)) - inv (Suc (Suc k + n)))/2) = inv (n+1)/2"
finally have "euler_mascheroni ≤ (∑k≤n. D k) + 1 / of_nat (2 * (n+1))"
also have "(∑k≤n. D k) = harm (Suc n) - (∑k≤n. ln (real_of_nat (Suc k+1)) - ln (of_nat (k+1)))"
unfolding harm_altdef D_def by (subst lessThan_Suc_atMost) (simp add:  sum.distrib sum_subtractf)
also have "(∑k≤n. ln (real_of_nat (Suc k+1)) - ln (of_nat (k+1))) = ln (of_nat (n+2))"
by (subst atLeast0AtMost [symmetric], subst sum_Suc_diff) simp_all
finally show "euler_mascheroni ≤ harm (Suc n) - ln (real_of_nat (n + 2)) + 1/real_of_nat (2 * (n + 1))"
by simp
qed

lemma euler_mascheroni_pos: "euler_mascheroni > (0::real)"
using euler_mascheroni_lower[of 0] ln_2_less_1 by (simp add: harm_def)

context
begin

private lemma ln_approx_aux:
fixes n :: nat and x :: real
defines "y ≡ (x-1)/(x+1)"
assumes x: "x > 0" "x ≠ 1"
shows "inverse (2*y^(2*n+1)) * (ln x - (∑k<n. 2*y^(2*k+1) / of_nat (2*k+1))) ∈
{0..(1 / (1 - y^2) / of_nat (2*n+1))}"
proof -
from x have norm_y: "norm y < 1" unfolding y_def by simp
from power_strict_mono[OF this, of 2] have norm_y': "norm y^2 < 1" by simp

let ?f = "λk. 2 * y ^ (2*k+1) / of_nat (2*k+1)"
define c where "c = inverse (2*y^(2*n+1))"
let ?d = "c * (ln x - (∑k<n. ?f k))"
have "⋀k. y⇧2^k / of_nat (2*(k+n)+1) ≤ y⇧2 ^ k / of_nat (2*n+1)"
by (intro divide_left_mono mult_right_mono mult_pos_pos zero_le_power[of "y^2"]) simp_all
moreover {
have "(λk. ?f (k + n)) sums (ln x - (∑k<n. ?f k))"
using sums_split_initial_segment[OF sums] by (simp add: y_def)
hence "(λk. c * ?f (k + n)) sums ?d" by (rule sums_mult)
also have "(λk. c * (2*y^(2*(k+n)+1) / of_nat (2*(k+n)+1))) =
(λk. (c * (2*y^(2*n+1))) * ((y^2)^k / of_nat (2*(k+n)+1)))"
also from x have "c * (2*y^(2*n+1)) = 1" by (simp add: c_def y_def)
finally have "(λk. (y^2)^k / of_nat (2*(k+n)+1)) sums ?d" by simp
} note sums' = this
moreover from norm_y' have "(λk. (y^2)^k / of_nat (2*n+1)) sums (1 / (1 - y^2) / of_nat (2*n+1))"
by (intro sums_divide geometric_sums) (simp_all add: norm_power)
ultimately have "?d ≤ (1 / (1 - y^2) / of_nat (2*n+1))" by (rule sums_le)
moreover have "c * (ln x - (∑k<n. 2 * y ^ (2 * k + 1) / real_of_nat (2 * k + 1))) ≥ 0"
by (intro sums_le[OF _ sums_zero sums']) simp_all
ultimately show ?thesis unfolding c_def by simp
qed

lemma
fixes n :: nat and x :: real
defines "y ≡ (x-1)/(x+1)"
defines "approx ≡ (∑k<n. 2*y^(2*k+1) / of_nat (2*k+1))"
defines "d ≡ y^(2*n+1) / (1 - y^2) / of_nat (2*n+1)"
assumes x: "x > 1"
shows   ln_approx_bounds: "ln x ∈ {approx..approx + 2*d}"
and     ln_approx_abs:    "abs (ln x - (approx + d)) ≤ d"
proof -
define c where "c = 2*y^(2*n+1)"
from x have c_pos: "c > 0" unfolding c_def y_def
by (intro mult_pos_pos zero_less_power) simp_all
have A: "inverse c * (ln x - (∑k<n. 2*y^(2*k+1) / of_nat (2*k+1))) ∈
{0.. (1 / (1 - y^2) / of_nat (2*n+1))}" using assms unfolding y_def c_def
by (intro ln_approx_aux) simp_all
hence "inverse c * (ln x - (∑k<n. 2*y^(2*k+1)/of_nat (2*k+1))) ≤ (1 / (1-y^2) / of_nat (2*n+1))"
by simp
hence "(ln x - (∑k<n. 2*y^(2*k+1) / of_nat (2*k+1))) / c ≤ (1 / (1 - y^2) / of_nat (2*n+1))"
with c_pos have "ln x ≤ c / (1 - y^2) / of_nat (2*n+1) + approx"
by (subst (asm) pos_divide_le_eq) (simp_all add: mult_ac approx_def)
moreover {
from A c_pos have "0 ≤ c * (inverse c * (ln x - (∑k<n. 2*y^(2*k+1) / of_nat (2*k+1))))"
by (intro mult_nonneg_nonneg[of c]) simp_all
also have "… = (c * inverse c) * (ln x - (∑k<n. 2*y^(2*k+1) / of_nat (2*k+1)))"
also from c_pos have "c * inverse c = 1" by simp
finally have "ln x ≥ approx" by (simp add: approx_def)
}
ultimately show "ln x ∈ {approx..approx + 2*d}" by (simp add: c_def d_def)
thus "abs (ln x - (approx + d)) ≤ d" by auto
qed

end

lemma euler_mascheroni_bounds:
fixes n :: nat assumes "n ≥ 1" defines "t ≡ harm n - ln (of_nat (Suc n)) :: real"
shows "euler_mascheroni ∈ {t + inverse (of_nat (2*(n+1)))..t + inverse (of_nat (2*n))}"
using assms euler_mascheroni_upper[of "n-1"] euler_mascheroni_lower[of "n-1"]
unfolding t_def by (cases n) (simp_all add: harm_Suc t_def inverse_eq_divide)

lemma euler_mascheroni_bounds':
fixes n :: nat assumes "n ≥ 1" "ln (real_of_nat (Suc n)) ∈ {l<..<u}"
shows "euler_mascheroni ∈
{harm n - u + inverse (of_nat (2*(n+1)))<..<harm n - l + inverse (of_nat (2*n))}"
using euler_mascheroni_bounds[OF assms(1)] assms(2) by auto

text ‹
Approximation of \<^term>‹ln 2›. The lower bound is accurate to about 0.03; the upper
bound is accurate to about 0.0015.
›
lemma ln2_ge_two_thirds: "2/3 ≤ ln (2::real)"
and ln2_le_25_over_36: "ln (2::real) ≤ 25/36"
using ln_approx_bounds[of 2 1, simplified, simplified eval_nat_numeral, simplified] by simp_all

text ‹
Approximation of the Euler-Mascheroni constant. The lower bound is accurate to about 0.0015;
the upper bound is accurate to about 0.015.
›
lemma euler_mascheroni_gt_19_over_33: "(euler_mascheroni :: real) > 19/33" (is ?th1)
and euler_mascheroni_less_13_over_22: "(euler_mascheroni :: real) < 13/22" (is ?th2)
proof -
have "ln (real (Suc 7)) = 3 * ln 2" by (simp add: ln_powr [symmetric])
also from ln_approx_bounds[of 2 3] have "… ∈ {3*307/443<..<3*4615/6658}"